Editorial Note - Dr. Sheila Ramalingam, (Journal of Malaysian and Comparative Law, 2023)
We end the year 2022 with the second issue of Volume 49 of the Journal of Malaysian and Comparative Law (JMCL). We are pleased to announce that starting from the first issue of Volume 49 published in June this year, JMCL is now available fully online via subscription. The previous volumes are fully accessible online without any subscriptions. This is to give JMCL more accessibility and visibility. Most importantly, it is to ensure that our articles reach audiences far and wide so as to impart, spread and share the valuable research and knowledge contributed by our authors.